PELATIHAN DASAR PENGGUNAAN APLIKASI MICROSOFT OFFICE DAN PAINT DI SEKOLAH DASAR NEGERI 1 UMEANYAR - Indrawan, Gede Beny; Sari, Gusti Ayu Gita Mulya; Putri, Kadek Utari Darma; Handayani Putri, Dwi Prima; Dewi, Luh Joni Erawati (Universitas Pendidikan Ganesha, 2022)
AbstractThis community service (P2M) activity was carried out purposefully to provides insight into the importance of technology, enhanced basic skills of operating computers, and enhanced skills in using the fundamental computer applications, such as Paint, Microsoft Office Word dan Microsoft Office Power Point for 4th, 5th, 6th grade student from Public Elementary School 1 Umeanyar. This activities was carried out by lectures method and discussion between the student and the speaker, followed by practice using computers to test student understanding about the material that has been presented before. The results ofthis activity are student understanding of the basics computer operation and skills in using fundamental computer applications, including the use of the Microsoft Power Point application to create interactive media products and the use of Microsoft Word to create documents, which are very useful as a provision for preparing themselves for higher education levels. Keywords : Gen A, ideal conditions, training, technology